How Agile Methods are Used and the Impact it has on Video Game Development (An Exploratory Study of PT. Agate International) - Kusumawardani, Farah Almira; Yudoko, Gatot (Journal of Business and Management, 2020)
Abstract. Agile methods are used more frequently in video game development which is a new yet promising creative economy sector that is developing in Indonesia. While it has many similarities to software engineering, video game development has its own set of challenges unique to it. However, the systematic use and impact of Agile in game development is largely undocumented. This research aims to provide an understanding of this issue specifically in PT. Agate International, one of the largest and most successful video game studios based in Indonesia, by doing a qualitative exploratory study of the Studio through the use of interviews and studying other documentary evidences by thestudio. The findings of this research show that PT. Agate International mainly uses Scrum (sometimes combined with Semi-Waterfall), Kanban, and Scrumban, matching the needs of the project it is used for, whereas some XP practices are used implicitly and is also adjusted to the type of project under way. The main positive impacts of Agile is on communication, facilitating the finding and change of features, improves quality of the game, on managing the scope of the project, as well as indirectly towards productivity of the development team.Keywords: Video game development, Scrum, XP, Agile methods and practices